Microbiological hazards associated with the use of water in the post‐harvest handling and processing operations of fresh and frozen fruits, vegetables and herbs (ffFVH). Part 3 (Fresh‐whole FVH process water management plan) - EFSA BIOHAZ Panel (EFSA Panel on Biological Hazards); Ana Allende; Avelino Alvarez‐Ordóñez; Valeria Bortolaia; Sara Bover‐Cid; Alessandra De Cesare; Wietske Dohmen; Laurent Guillier; Lieve Herman; Liesbeth Jacxsens; Lapo Mughini‐Gras; Maarten Nauta; et al. (EFSA Journal)
Abstract Water used in post‐harvest handling and processing operations is an important risk factor for microbiological cross‐contamination of fruits, vegetables and herbs (FVH). Industrial data indicated that the fresh‐whole FVH sector is characterised by very variable operational cycle duration (between 8 and 900 h), large product volumes (e.g. more than 6000 tonnes) and process water at 2.8–25.0°C. Intervention strategies were based on water disinfection treatments, mostly using chlorine‐based disinfectants. Water replenishment was not observed within studied industries. The industrial data, which included 29 scenarios were used to develop a guidance for a water management plan (WMP) for the fresh‐whole FVH sector. A WMP aims to maintain the fit‐for‐purpose microbiological quality of the process water and consists of (a) identification of microbial hazards and hazardous events linked to process water; (b) establishment of the relationship between microbiological and physico‐chemical parameters; (c) description of preventive measures; (d) description of intervention measures, including their validation, operational monitoring and verification; and (e) record keeping and trend analysis. A predictive model was used to simulate water management outcomes, highlighting the need for water disinfection treatments to maintain the microbiological quality of the process water and the added value of water replenishment. Relying solely on water replenishment (at realistic feasible rates) does not avoid microbial accumulation in the water. Operational monitoring of the physico‐chemical parameters ensures that the disinfection systems are operating effectively. Verification includes microbiological analysis of the process water linked to the operational monitoring outcomes of physico‐chemical parameters. Food business operators (FBOps) should set up and validate a tailored WMP to identify physico‐chemical parameters, as well as microbial indicators and their threshold levels, as performance standards for maintaining the fit‐for‐purpose microbiological quality of the process water during post‐harvest handling and processing operations.